Efficient conversion of a nonselective norepinephrin reuptake inhibitor into a dual muscarinic antagonist-β₂-agonist for the treatment of chronic obstructive pulmonary disease - Osborne, Rachel; Clarke, Nick; Glossop, Paul; Kenyon, Amy; Liu, Hao; Patel, Sheena; Summerhill, Susan; Jones, Lyn H (Journal of medicinal chemistry, 2011)
Following interrogation of a wide-ligand profile database, a nonselective norepinephrin reuptake inhibitor was converted into a novel muscarinic antagonist using two medicinal chemistry transformations (M3/NRI selectivity of >1000). Conjugation to a β(2) agonist motif furnished a molecule with balanced dual pharmacology, as demonstrated in a guinea pig trachea tissue model of bronchoconstriction. This approach provides new starting points for the treatment of chronic obstructive pulmonary disease and illustrates the potential for building selectivity into GPCR modulators that possess intrinsic promiscuity or reverse selectivity.